Variation of the boat velocity - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
The article investigates the old and widely spread idea, that the variation of the boat velocity during the stroke cycle is the main factor of energy loss and must be reduced for efficient rowing. Its reasoning is the following: Energy losses due to drag resistance are proportional to the cube of boat velocity. When thinking about the problem it is important to know that Variation of the boat velocity in rowing has only two reasons: 1. Periodic nature of the propulsion. Blades produce propulsive force only during the drive phase - about half of the stroke cycle time. Therefore, the rower-boat system accelerates during the drive, and slowing down during recovery. 2. Significant movements of the rower`s mass, which is much heavier (4-6 times) than the boat mass.